Seldinger technique in repair of the parotid duct. Issue 1 (January 2019) - Hills, A.J.; Kannan, R.Y.; Williams, M.
Abstract: Injuries to the parotid ducts are difficult to locate, assess, and repair, and traditionally, solid metal dilators and soft plastic tubes have had only limited success. We describe the Seldinger technique with a central venous catheter, which makes repair easier.